2017
DOI: 10.1371/journal.pone.0177434
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based peer support for mothers to improve their breastfeeding practices: A systematic review and meta-analysis

Abstract: Breastfeeding is associated with reduced mortality in children aged less than 5 years. We conducted a systematic review and meta-analysis (registered as PROSPERO 2015: CRD42015019105) to examine the effectiveness of community-based peer support for mothers on their breastfeeding practices as compared to mothers who have not received such a support.MethodsWe searched for evidence regarding community-based peer support for mothers in databases, such as PubMed/MEDLINE, the Cochrane Library, CINAHL, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 49 publications
(105 reference statements)
1
99
0
5
Order By: Relevance
“…This context is different from that observed in underdeveloped and developing countries where socioeconomic aspects may justify the higher prevalence of children with low Birth Weight, such as when comparing South America with Europe [21]. Breastfeeding patterns are also different in distinct countries and cultures and depend on socio-cultural support for their success [30], which may justify controversial results found among different studies. Therefore, considering the various factors involved in VO 2max , in Birth Weight and in breastfeeding patterns of children, it is concluded that the present cross-sectional study, performed in individuals with adequate Birth Weight and gestational age, contributes to the current body of scientific knowledge about population and to assist in the planning of public health actions and in the clinical practice of professionals dealing with children and adolescents.…”
Section: Discussionmentioning
confidence: 85%
“…This context is different from that observed in underdeveloped and developing countries where socioeconomic aspects may justify the higher prevalence of children with low Birth Weight, such as when comparing South America with Europe [21]. Breastfeeding patterns are also different in distinct countries and cultures and depend on socio-cultural support for their success [30], which may justify controversial results found among different studies. Therefore, considering the various factors involved in VO 2max , in Birth Weight and in breastfeeding patterns of children, it is concluded that the present cross-sectional study, performed in individuals with adequate Birth Weight and gestational age, contributes to the current body of scientific knowledge about population and to assist in the planning of public health actions and in the clinical practice of professionals dealing with children and adolescents.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, this study demonstrates one-to-one peer counselling may be an effective strategy to improve EIBF and EBF practices in urban slum communities, where a high rate of malnutrition exists and inappropriate breastfeeding practices are prominent (Shakya et al, 2017 group counselling may be effective to increase the rates of EIBF and EBF (Haider et al, 2000). Governments and NGOs could even consider training community health volunteers to provide group or peer support on infant and young child feeding practices to the mothers and caregivers.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, this study demonstrates one‐to‐one peer counselling may be an effective strategy to improve EIBF and EBF practices in urban slum communities, where a high rate of malnutrition exists and inappropriate breastfeeding practices are prominent (Shakya et al, ). Our peer counsellors delivered a regular service on a part‐time (half‐day) basis and received a monthly honorarium of approximately US $43.…”
Section: Discussionmentioning
confidence: 88%
“…In most countries, a variety of intervention delivery platforms, or channels, are used to reduce access barriers to essential services. Notable examples are trained community health workers (CHWs) and mother/peer groups for health and nutrition promotion [7][8][9]. Though evidence supports CHW home visits and women's groups for improving maternal and newborn health in low and middle-income countries (LMICs) [10][11][12], evidence from high-quality studies involving such community platforms for delivering nutrition-specific interventions is limited across diverse populations [5].…”
Section: Introductionmentioning
confidence: 99%